PENGARUH MOTIVASI KERJA DAN STRES TERHADAP KEPUASAN KERJA PADA PT. DELTA MULTI MANDIRI MEDAN - Sutanto, Alex (UNIKA Santo Thomas, 2018)
PT. Multi Mandiri Medan is one of the companies engaged in the field of labor services namely clearning service and security guard. Employees feel less satisfied, because the form of motivation provided by the company is not as expected by the employee. In addition, employees experience stress due to excessive workloads, remuneration provided is not proportional to the workload provided by superiors and superiors are not being fair to subordinates. This study aims to determine and analyze the influence of motivation and stress on job satisfaction at PT. Delta Multi Mandiri Medan. The benefits of research is to provide information to the leadership of the influence of motivation and stress on job satisfaction. The research population is all employees of PT. Delta Multi Mandiri Medan as many as 68 people. In this research, the research sample counted 68 people. The data used in this study is primary data collected through questionnaires. Data analysis technique used is descriptive analysis and multiple linear regression analysis and hypothesis test. The result of t test shows that motivation has positive and significant effect partially on job satisfaction; while the stress variable has a negative and significant effect on job satisfaction at PT. Delta Multi Mandiri Medan. F test results show that motivation and stress significantly influence simultaneously to job satisfaction at PT. Delta Multi Mandiri Medan. Based on the results of the discussion, obtained multiple linear regression equation obtained is Y = 12.45 + 0.898.X1 - 0.253.X2. That is, motivation and stress affect the job satisfaction at PT. Delta Multi Mandiri Medan. This can be seen from the value of the regression coefficient. In other words, if the form of motivation increases, then job satisfaction will increase. However, if the cause of stress increases, employee job satisfaction will decrease. The value of the correlation coefficient (RÂ²) is 0.804. That is, motivation and stress have a strong relationship to job satisfaction at PT. Delta Multi Mandiri Medan.